(untitled) (American Journal of Islam and Society, 2014)
The International Islamic University, Malaysia’s (IIUM) Department of Usul al-Din and Comparative Religion, along with the Kulliyyah of Islamic Revealed Knowledge and Human Science (IRKHS), organized an international conference to analyze the work of Ismail Raji al-Faruqi, a leading twentiethcentury thinker who had had a significant impact on Islamic thought and comparative religion. Held at IIUM’s Senate Hall on October 22-23, 2013, in collaboration with Kolej Universiti Islam Sultan Azlan Shah (KUISAS), participants discussed the legacy of this influential scholar, who is best known for his pioneering work in the Islamization of Knowledge movement. One of his books, Al Tawhid: Its Implications for Thought and Life (Herndon, VA: IIIT, 1992) has attracted the attention of scholars and been introduced into various university courses worldwide as an important resource book. The main theme was “Infusing the Creativity and Excellence of al-Faruqi’s Scholarship into Contemporary Islamic Thought.” The seventy-five accepted papers were divided into five sub-themes: tawḥīd, the Islamization of Knowledge, Islamic civilization, Islamic thought, and comparative religion. The organizers invited scholars to (1) study and examine the relevance of al-Faruqi’s thought, (2) examine his vision and mission in various areas of Islamic thought, (3) regenerate the tradition of Islamic scholarship in academic disciplines, (4) enhance the intellectual understanding of Islam’s tawhidic worldview, and (5) develop a comparative approach to the study of Islamic thought in relation to modernity. This unique event enabled scholars, intellectuals, and academicians to meet and deliberate on al-Faruqi’s intellectual and scholarly output. This event began with three inaugural speeches. Zambry Bin Abdul Kadir (chief minister, State of Perak) pointed out that only intellectual and moral development can cause human civilization to reach its zenith. In the case of Islamic civilization, this development was achieved by grounding the civilization on the core values of research, criticism, and creativity. He stated that al-Faruqi dedicated his life to calling upon Muslims to revive that sprit. Ibrahim M. Zein (dean, IRKHS) highlighted the conference’s importance and expressed his hope that it would be a resounding success. Mohamed Ridza Wahiddin (deputy rector, Research and Innovation, IIUM) called for excellence and innovation in contemporary Muslim scholarship and emphasized that tawḥīd and the tawhidicworldview must be the base of Islamic discourse. He further remarked ...